2020
DOI: 10.1007/s00421-020-04481-8
|View full text |Cite
|
Sign up to set email alerts
|

Water immersion methods do not alter muscle damage and inflammation biomarkers after high-intensity sprinting and jumping exercise

Abstract: The aim of this study was to compare the efficacy of three water immersion interventions performed after active recovery compared to active recovery only on the resolution of inflammation and markers of muscle damage post-exercise. Methods Nine physically active men (n = 9; age 20-35 years) performed an intensive loading protocol, including maximal jumps and sprinting on four occasions. After each trial, one of three recovery interventions (10 min duration) was used in a random order: cold-water immersion (CWI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In contrast to these investigations, de Andrade Bezerra et al (2014) found no effect of recovery by cold-water immersion (10 °C, 10 min, immersion to the iliac crest level) on leukocyte count, after a soccer match. Also, no effect was found for leukocyte counts, C-reactive protein and markers of muscular damage after cold-or thermoneutral-water (24 °C) immersion following a high-intensity sprint and jumping exercise protocol and active recovery Ahokas et al (2020). Again, the leukocyte response to the exercise stress in the cited studies is qualitatively different from ours (both Ahokas et al, 2020 andde Andrade Bezerra et al, 2014) observed lymphopenia after exercise), and this leads us to argue whether the effect of water immersion on leukocytes is dependent on the dynamics of the leukocyte response to the exercise.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In contrast to these investigations, de Andrade Bezerra et al (2014) found no effect of recovery by cold-water immersion (10 °C, 10 min, immersion to the iliac crest level) on leukocyte count, after a soccer match. Also, no effect was found for leukocyte counts, C-reactive protein and markers of muscular damage after cold-or thermoneutral-water (24 °C) immersion following a high-intensity sprint and jumping exercise protocol and active recovery Ahokas et al (2020). Again, the leukocyte response to the exercise stress in the cited studies is qualitatively different from ours (both Ahokas et al, 2020 andde Andrade Bezerra et al, 2014) observed lymphopenia after exercise), and this leads us to argue whether the effect of water immersion on leukocytes is dependent on the dynamics of the leukocyte response to the exercise.…”
Section: Discussionmentioning
confidence: 90%
“…Also, no effect was found for leukocyte counts, C-reactive protein and markers of muscular damage after cold-or thermoneutral-water (24 °C) immersion following a high-intensity sprint and jumping exercise protocol and active recovery Ahokas et al (2020). Again, the leukocyte response to the exercise stress in the cited studies is qualitatively different from ours (both Ahokas et al, 2020 andde Andrade Bezerra et al, 2014) observed lymphopenia after exercise), and this leads us to argue whether the effect of water immersion on leukocytes is dependent on the dynamics of the leukocyte response to the exercise. In our study, we did not observe effects of cold-or thermoneutral-water immersion on leukocyte counts, although both water temperatures, beyond 38 °C modified the composition of lymphocyte and monocyte subsets after the experimental exercise.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Belief stems from positive reductions in secondary cell injury and/or reducing inflammation following injury in animal models [59]. However, whilst some research shows post-exercise CWI might positively influence some markers of inflammation post-exercise [60,61], there remains a substantial contrasting volume of research showing a neutral effect, whereby CWI has no influence in moderating the post-exercise inflammatory response [15,[62][63][64][65][66]. This is supported further by cellular and molecular investigations [58].…”
Section: Current Knowledge Of Benefits and Associated Physiological Mechanismsmentioning
confidence: 99%
“…The most reported mechanisms associated with benefits of CWI were cardiovascular alterations in blood flow and constriction of blood vessels. To date, a significant amount of work has demonstrated reduced limb blood flow, or reduced blood volume, across the exercised muscle following CWI [47,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. However, more recent data [71] employing positron emission tomography (PET) with an oxygen-15-labelled water radiotracer ([ 15 O]H 2 O) suggests that application of noxious water temperatures (< 8 °C) may actually result in less pronounced reductions in muscle perfusion compared with less noxious (15 °C) immersion (under resting conditions).…”
Section: Current Knowledge Of Benefits and Associated Physiological Mechanismsmentioning
confidence: 99%